Parental Counseling in Fostering Mathematics Learning of Elementary School Children in Pojok Hamlet, Campurdarat District, Tulungagung Regency: Penyuluhan Orang Tua dalam Membimbing Belajar Matematika Anak Sekolah Dasar di Dusun Pojok Kecamatan Campurdarat, Kabupaten Tulungagung - Anggreini, Dewi; Hayuhantika, Diesty; Hairunisya, Nanis (Mattawang: Jurnal Pengabdian Masyarakat, 2020)
Parents play an important role in education, because they can help develop children’s learning potential and become a determining factor for the child’s future. Children must be given the best education from an early age, so that it can have a positive impact on children when they become students at school. The purpose of this service was to determine the importance of learning mathematics, to motivate and foster children’s interest in mathematics, to determine on how to help children in learning mathematics properly, to determine the practical and humanist mathematics learning knowledge, and to provide the appropriate and fun learning methods for children. In this service activity, there were several problems encountered in Pojok Hamlet, among others, parents had limited ability and time to foster children’s mathematics learning, children had difficulty in understanding mathematics, parents were not confident in fostering their children to learn mathematics. The methods used in the implementation of this activity were the lecture and question and answer methods. This service activity was attended by parents of grade 2 and 3 at SDN 3 Pojok, Campurdarat District. Based on the results of questionnaires and interviews conducted in this service activity, it was found that parents were very enthusiastic and their knowledge increased after attending the counseling. There was an increase in the frequency of parents in fostering and helping their children to study at home. Referring to the results of this counseling activity, it can be concluded that parents should provide mathematical knowledge from an early age to their children, specifically for early grade children, particularly grades 1, 2, and 3. Basic mathematical knowledge can be used as a provision for skills for parents in assisting their children to learn mathematics. Parents can use mathematics teaching aids in the neighborhood in fostering their children to learn mathematics about addition, multiplication and division. Abstrak Peran orangtua terhadap pendidikan sangatlah penting karena membantu perkembangan belajar anak dan menjadi salah satu faktor penentu masa depan anak. Sejak dini anak-anak harus diberikan pendidikan yang terbaik agar memberikan dampak positif bagi anak didik. Tujuan pengabdian ini adalah mengetahui pentingnya belajar ilmu matematika, memotivasi dan menumbuhkan minat anak terhadap matematika, mengetahui bagaimana cara mendampingi anak belajar matematika dengan baik, mengetahui pengetahuan belajar matematika yang praktis dan humanis dan metode belajar yang tepat dan menyenangkan bagi anak. Permasalahan yang dihadapi di dusun Pojok yaitu orang tua mempunyai keterbatasan kemampuan dan waktu dalam membimbing belajar matematika anak, anak mengalami kesulitan dalam memahami matematika, orang tua tidak percaya diri membimbing anak belajar matematika. Metode pelaksanaan kegiatan berupa ceramah dan tanya jawab. Kegiatan pengabdian ini diikuti oleh orang tua siswa kelas 2 dan 3 SDN 3 Pojok Kecamatan Campurdarat. Kegiatan pengabdian ini diperoleh beberapa hasil yaitu dari hasil angket dan wawancara, orang tua sangat antusias dan pengetahuannya bertambah setelah mengikuti pelatihan. Terjadi peningkatan frekuensi orang tua dalam membimbing dan membantu putra-putrinya belajar di rumah. Orang tua hendaknya memberikan pengetahuan matematika sejak dini bagi anak khususnya untuk anak kelas awal yaitu kelas 1, 2, dan 3. Pengetahuan matematika dasar dapat dijadikan bekal keterampilan bagi orang tua dalam mendampingi anak-anaknya belajar matematika. Orang tua bisa menggunakan alat peraga matematika yang ada di lingkungan sekitar dalam membimbing putra putrinya belajar matematika tentang penjumlahan, perkalian dan pembagian.